2001
DOI: 10.1002/pola.10096
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of biodegradable poly(ϵ‐caprolactone urethane)s. I. Effect of the polyol molecular weight, catalyst, and chain extender on the molecular and physical characteristics

Abstract: Biodegradable polyurethanes with potential for applications in medical implants were synthesized in bulk with aliphatic hexamethylene diisocyanate, isophorone diisocyanate, poly(ϵ‐caprolactone) diols of various molecular weights, 1,4‐butane diol, 2‐amino‐1‐butanol, thiodiethylene diol, and 2‐mercaptoethyl ether chain extenders. The catalysts used were stannous octoate, dibutyltin dilaurate, ferric acetyl acetonate, magnesium methoxide, zinc octoate, and manganese 2‐ethyl hexanoate. The synthesis reactions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 33 publications
0
56
2
Order By: Relevance
“…However, the compressive strength (i.e., the compressive stress measured at 50% strain) of the HDIt and LTI materials (5-15 kPa) was higher than that of the LDI materials (2-4 kPa). HDI-prepolymer foams of comparable density (80-107 kg m −3 ) from a previous study were generally stronger than the one-shot HDIt and LTI foams of the present study, with compressive strengths of 30-85 kPa (at 40% strain) versus 5-15 kPa (at 50% strain) for the HDIt and LTI foams (44,45). However, the Young's moduli of the HDI-prepolymer foams are lower, at 9-21 kPa, compared to 26-202 kPa for the one-shot foams.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, the compressive strength (i.e., the compressive stress measured at 50% strain) of the HDIt and LTI materials (5-15 kPa) was higher than that of the LDI materials (2-4 kPa). HDI-prepolymer foams of comparable density (80-107 kg m −3 ) from a previous study were generally stronger than the one-shot HDIt and LTI foams of the present study, with compressive strengths of 30-85 kPa (at 40% strain) versus 5-15 kPa (at 50% strain) for the HDIt and LTI foams (44,45). However, the Young's moduli of the HDI-prepolymer foams are lower, at 9-21 kPa, compared to 26-202 kPa for the one-shot foams.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, enzymatic cleavage of the lysine residues likely contributes to accelerated degradation of the LTI scaffolds in vivo (48). Previous studies have shown that the addition of PEG increases the hydrolytic degradation rate, presumably due to the increased hydrophilicity with PEG (38,(44)(45)(46). The addition of PEG 600 to HDIt foams increased the initial degradation rate (1-8 weeks), which is attributed to increased bulk hydrophilicity resulting from higher PEG content.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the SPURs derived from PHCD, which were plasticized in slightly higher temperatures, exhibited somewhat higher molar-mass dispersity compared with those from PTMO (see pressing temperature in Table 6). Polymers with similar molar-mass dispersity were also obtained by other authors [18,28,29]. Table 1 Designations, g red , GPC, transmittance, and refractive index data of the SPURs The chemical structures of all the SPURs were examined by elemental analysis and ATR-FTIR spectroscopy.…”
Section: Resultsmentioning
confidence: 93%
“…In the last decade only a few articles containing comprehensive studies on thermoplastic poly(thiourethane) elastomers [10] and poly(thiourethane-urethane) elastomers (EPTURs) [11][12][13][14], as well as crosslinked ones [15], have been published.…”
mentioning
confidence: 99%